Malaysian copyright law in the digital environment: Does it provide a balance of interests between copyright owners and the public? / Sik Cheng Peng - Sik , Cheng Peng (2016)
Copyright law encourages authors to create and share their works with the public by affording them legal protection over their works when published. However, copyright law does not give authors absolute rights so as to ensure that the public will benefit from the works produced by authors. In this way, copyright law promotes the progress of arts and science. The importance of maintaining a balance of interests between copyright owners and the public is widely acknowledged and emphasized in international treaties on intellectual property rights as well as by the courts in case law. The development of digital technologies has brought substantial challenges to copyright law. The process of copying and sharing of digital works is made extremely easy and at low cost. Copyright owners have thus lobbied for stronger protection under copyright law and succeeded in doing so. It is therefore crucial to study how copyright law accommodates the issues raised by digital technologies and whether it provides a balance of interests between copyright owners and the public in doing so. This thesis examines the application of Malaysian copyright law in addressing the issues arising in relation to digital technologies and whether it maintains a balance of interests between copyright owners and the public in the digital environment. The advent of digital technologies has raised a wide range of copyright concerns. This thesis looks into the questions in five selected areas, namely, digital appropriation of copyright works, the setting of links on websites, peer-to-peer file sharing, the limitation of liabilities of service providers and legal protection over technological protection measures. This thesis analyzes the Copyright Act 1987, being the statute governing copyright matters in Malaysia. It also makes reference to three main jurisdictions, namely, the United States, the United Kingdom and Australia, wherever it is necessary and relevant. Malaysian copyright law is inadequate and insufficient in many ways in addressing the issues in the identified areas. Overall, Malaysian copyright law tilts in favour of copyright owners at the expense of public interest. This thesis concludes with recommendations on how Malaysian copyright law may handle the issues raised by digital technologies more adequately and efficiently, with the ultimate object of striking a balance between the interests of copyright owners and the public.